2015
DOI: 10.4172/2155-6156.1000570
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Prevalence and Predictors of Obesity in Urban and Rural Communities in Abia State South Eastern Nigeria

Abstract: Background and objectives: Obesity is assuming an epidemic dimension globally. Currently more than 1.9 billion adults are overweight-and at least 600 million of them are obese. There is dearth of community based study on prevalence and predictors of obesity in Nigeria, and none from Abia state in particular, prompting us to undertake the study. Material and Methods: This was a cross-sectional study, aimed at ascertaining the prevalence and predictors of obesity in the state. The study subjects were recruited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 10 publications
3
17
2
Order By: Relevance
“…On the contrary, the prevalence of overweight 38.4% and obesity 21.5% noted in this study are similar to those reported in two studies, one in Brazil [10], the other in USA [22]. These, including our findings, are similar to the BMI reported in a general population in Eastern Nigeria [23]. The high prevalence of obesity observed in our study in subjects who were not on HAART, might be explained by a background high prevalence of obesity in the general population [23].…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, the prevalence of overweight 38.4% and obesity 21.5% noted in this study are similar to those reported in two studies, one in Brazil [10], the other in USA [22]. These, including our findings, are similar to the BMI reported in a general population in Eastern Nigeria [23]. The high prevalence of obesity observed in our study in subjects who were not on HAART, might be explained by a background high prevalence of obesity in the general population [23].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, this is higher than the 2.5% documented by Chukwuonye et al [16] in Abia State, Nigeria. Both studies were done in the same Southeast geopolitical zone of Nigeria.…”
Section: Discussioncontrasting
confidence: 53%
“…[9] It was, however, lower than the 28.2% and 38.4% reported in two Nigerian studies. [16,25] The first study was community-based, the second HIV clinicbased, while ours was hospital-based: this might be the reason for the difference in the prevalence of overweight compared to that noted in our study.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations